ONLINE APPLICATION BASED ON KING INTERACTION SYSTEM THEORY TO INCREASE TREATMENT ADHERENCE AND CLINICAL INDICATORS IN TB CHILDREN - Sari, Ethyca; Nur Kristina, Tri; Sujianto, Untung; Suhartono; Sakti, Hastaning (The Indonesian Journal of Public Health, 2024)
Introduction:  Non-adherence to treatment among TB children in Indonesia varied 40.5%-57.2%. An innovative method of education might improve treatment adherence and clinical recovery of TB children. The aims of this study were to compare the treatment adherence and clinical indicators of TB children who received an intervention using an online application based on King's theory with a conventional method. Methods: This is a quasi-experimental study to educate 55 TB school-age children using a validated online application based on King's interaction system theory, compared with the conventional method in 55 TB children as the control group. The medication regularity and control discipline were observed four times in weeks 2, 4, 6, and 8. Measurements of acid-fast bacilli (AFB) smear sputum examination, TB scoring, chest X-ray examination, level of Hb, and nutritional status were done twice in pre- and post-intervention. Data analysis used chi-square, paired t-test, independent t-test, Mann Whitney, McNemarᵇ. or Wilcoxon test. Results: The results of this study revealed that the intervention group was significantly successful compared to the control group in several indicators, such as increasing treatment adherence (p=0.001), controlling discipline (p=0.001), reducing AFB positive (p=0.001), TB scoring (p=0.001), infiltrate in chest X-ray examination ((p=0.013), and increasing Hb levels (p=0.001). Meanwhile, nutritional status could not be compared because, from the beginning of the study, the nutritional status was unbalanced and benefited the intervention group. Conclusion: The online application based on King's theory has succeeded in increasing medication adherence and clinical improvement of pulmonary TB in children.